BIODEGRADATION OF CHEMICALLY MODIFIED EGG ALBUMIN MICROPREPARATION FOR CONTROLLED RELEASE OF BOUND VIGNA MUNGO AMYLASE AND THEIR APPLICATION IN FABRIC DESIZING AS COST EFFECTIVE BIO-ACTIVE PREPARATION - KIRTI RANI; NAMRATA PANT; CHANCHAL CHAUHAN (International Journal of Pharma and Bio Sciences, 2015)
In our present work, purified and thermally stable Vigna mungo amylase was entrapped into toluene modified egg albumin microparticles through covalent coupling by glutaraldehyde. Biodegradation of chemically modified egg albumin microparticles was carried out by using various units of alkaline protease (5U, 10U, 15U, 20U, 25U, 30U, 35U, 40U) for the controlled and sustained release of entrapped enzymes from prepared microparticles. Enzyme storage stability was found to be increased up to 6 months as well as thermal stability, enhanced up to 72ºC as compared to free enzyme (24 hours only and 40ºC respectively). Further, this chemically modified enzyme loaded egg albumin microparticles along with studied effective units of alkaline protease was used with different samples of market available detergents powder (Aerial, Surf Excel, Wheel and Tide) for washing of tough and dry lipstick stained cloths pieces having strains of well known brands (Revlon, Maybelline, Lakme and Dior). These lipstick strains are ,sometimes, used to be very difficult to leach out form fabrics and, usually, not to vanishin one wash while they were used to be soaked in lukewarm tap water too when washed with well known brands of commercially available washing powders. But, this cost effective enzyme loaded bio-active micropreaparation with alkaline protease were used with chosen detergents powder for washing of these dry, tough lipstick stains lead to vanishing those strains very fast with absolute clear visible results when, their results were compared to results of washing of stained cloths pieces with detergents only.